Mitogen-Activated Protein Kinase OsMEK2 and OsMPK1 Signaling Is Required for Ferroptotic Cell Death in Rice–Magnaporthe oryzae Interactions - Dangol, Sarmina; Nguyen, Nam Khoa; Singh, Raksha; Chen, Yafei; Wang, Juan; Lee, Hyeon-Gu; Hwang, Byung KooK; Jwa, Nam-Soo (Frontiers in Plant Science, 2021)
Mitogen-activated protein kinase (MAPK) signaling is required for plant cell death responses to invading microbial pathogens. Iron- and reactive oxygen species (ROS)-dependent ferroptotic cell death occurs in rice (Oryza sativa) during an incompatible rice–Magnaporthe oryzae interaction. Here, we show that rice MAP kinase (OsMEK2 and OsMPK1) signaling cascades are involved in iron- and ROS-dependent ferroptotic cell death responses of rice to M. oryzae infection using OsMEK2 knock-out mutant and OsMEK2 and OsMPK1 overexpression rice plants. The OsMPK1:GFP and OsWRKY90:GFP transcription factor were localized to the nuclei, suggesting that OsMPK1 in the cytoplasm moves into the nuclei to interact with the OsWRK90. M. oryzae infection in ΔOsmek2 knock-out plants did not trigger iron and ROS accumulation and lipid peroxidation, and also downregulated OsMPK1, OsWRKY90, OsRbohB, and OsPR-1b expression. However, 35S: OsMEK2 overexpression induced ROS- and iron-dependent cell death in rice. The downstream MAP kinase (OsMPK1) overexpression induced ROS- and iron-dependent ferroptotic cell death response to virulent M. oryzae infection. The small-molecule ferroptosis inhibitor ferrostatin-1 suppressed iron- and ROS-dependent ferroptotic cell death in 35S:OsMPK1 overexpression plants. However, the small-molecule inducer erastin triggered iron- and lipid ROS-dependent, but OsMEK2-independent, ferroptotic cell death during M. oryzae infection. Disease (susceptibility)-related cell death was lipid ROS-dependent, but iron-independent in the ΔOsmek2 knock-out mutant during the late M. oryzae infection stage. These combined results suggest that OsMEK2 and OsMPK1 expression positively regulates iron- and ROS-dependent ferroptotic cell death, and blast disease (susceptibility)-related cell death was ROS-dependent but iron-independent in rice-M. oryzae interactions.